Untypical Metabolic Adaptations in Spontaneously Hypertensive Rats to Free Running Wheel Activity Includes Uncoupling Protein-3 (UCP-3) and Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9) Expression - Wolf, Annemarie; Kutsche, Hanna Sarah; Atmanspacher, Felix; Karadedeli, Meryem Sevval; Schreckenberg, Rolf; Schlüter, Klaus-Dieter (Frontiers in Physiology, 2021)
Obesity and hypertension are common risk factors for cardiovascular disease whereas an active lifestyle is considered as protective. However, the interaction between high physical activity and hypertension is less clear. Therefore, this study investigates the impact of high physical activity on the muscular and hepatic expression of glucose transporters (Glut), uncoupling proteins (UCPs), and proprotein convertase subtilisin/kexin type 9 (PCSK9) in spontaneously hypertensive rats (SHRs). 24 female rats (12 normotensive rats and 12 SHRs) were divided into a sedentary control and an exercising group that had free access to running wheels at night for 10 months. Blood samples were taken and blood pressure was determined. The amount of visceral fat was semi-quantitatively analyzed and Musculus gastrocnemius, Musculus soleus, and the liver were excised. Acute effects of free running wheel activity were analyzed in 15 female SHRs that were sacrificed after 2 days of free running wheel activity. M. gastrocnemius and M. soleus differed in their mRNA expression of UCP-2, UCP-3, Glut-4 and PCSK9. Hypertension was associated with lower levels of UCP-2 and PCSK9 mRNA in the M. gastrocnemius, but increased expression of Glut-1 and Glut-4 in the M. soleus. Exercise down-regulated UCP-3 in the M. soleus in both strains, in the M. gastrocnemius only in normotensives. In SHRs exercise downregulated the expression of UCP-2 in the M. soleus. Exercise increased the expression of Glut-1 in the M. gastrocnemius in both strains, whereas it increased the muscle-specific expression of PCSK9 only in normotensive rats. Effects of exercise on the hepatic expression of cholesterol transporters were seen only in SHRs. None of these effects were found as an acute response to exercise. This study, based on transcriptional adaptations in striated muscles and liver, shows that rats perform long-term metabolic adaptations when kept with increased physical activity. However, normotensive and hypertensive rats differed in their responsiveness. Based on these results, a direct translation from normotensive to hypertensive rats is not possible. As genetic differences between normotensive humans and patients with essential hypertension are likely to be present as well, we would expect similar differences in humans that may impact recommendations for non-pharmacological interventions.